INTEGRATING ARTIFICIAL INTELLIGENCE AND HUMANISTIC VALUES IN ISLAMIC ELEMENTARY EDUCATION: A CASE STUDY AT MADRASAH IBTIDAIYAH NU MA’ARIF KARANGNANGKA - Donny Khoirul Azis; Irfan Musonif; Syifa Salsabila; Minan Ainur Fatah; Muchammad Aji (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
The integration of artificial intelligence (AI) in education presents both opportunities and ethical challenges, particularly within Islamic education, which emphasizes moral and spiritual values. However, empirical studies examining how AI is humanistically integrated in madrasah contexts remain limited. This study aims to analyze the process of AI integration within value-based Islamic pedagogy and to construct a conceptual Humanistic–AI Learning Model for Islamic elementary education. A qualitative case study was conducted at Madrasah Ibtidaiyah NU Ma’arif Karangnangka, Banyumas, involving five teachers, one principal, and three students selected purposively. Data were collected through semi-structured interviews, participatory observations, and document analysis, and analyzed thematically using Miles and Huberman’s interactive model with triangulation. The findings indicate that AI integration operates as a negotiation between technological literacy and spiritual values. Four themes emerged: (1) the initial construction of AI as an instrumental tool, (2) partial yet humanistically oriented digital pedagogical practices, (3) ethical tensions between technological efficiency and moral integrity, and (4) the role of spiritual leadership in shaping digital transformation. This study contributes a novel Humanistic–AI Learning Model that conceptualizes a dialectical relationship between pedagogical, humanistic, and spiritual dimensions in AI integration. The model extends humanistic learning perspectives by framing AI as an ethical-spiritual practice and provides practical implications for developing ethically grounded, AI-ready madrasahs.